University Students and Their Concerns: Prevalence and Degree of Severity - Setiawan, Jenny Lukito (Faculty of Psychology, Universitas Surabaya, 2008)
Since undergraduates are moving from adolescence to young adulthood, they face many changes in this transitional period. It is argued that they still need support to “grow’ and cope with all the “unbearable” stresses. The aim of this study is to assess the prevalence and degree of severity of students’ concerns during their university career. Participants (N = 1,279) were students from two universities, who volunteered to complete self-administered questionnaires. Results reveal that aca- demic-related problems were the most widely experienced and the most serious concerns for stu- dents, compared to other areas. With regard to the prevalence of concerns, problems related to aca- demic, self, depression and mood change, romantic relationships, welfare, other relationships, anxie- ty, loss, and transitions, were experienced by more than 50% of students participating in the study. Detailed findings, implications of results, and the recommendation for improving the quality of uni- versity students life are further discussed Karena mahasiswa S-1 adalah remaja yang menuju dewasa muda, mereka menghadapi banyak perubahan dalam masa transisi ini. Diasumsikan bahwa mereka masih membutuhkan dukungan untuk “tumbuh” dan mengatasi berbagai stres yang berat. Tujuan penelitian ini adalah me- nilai prevalensi dan beratnya keprihatinan mahasiswa selama masa studinya. Partisipan penelitian ini (N = 1,279) adalah mahasiswa dua perguruan tinggi, yang bersedia mengisi kuesioner tentang pribadinya. Hasil mengungkapkan bahwa masalah terkait-akademik merupakan yang paling banyak dialami dan paling serius bagi para mahasiswa, dibandingkan hal lain. Menyangkut prevalensi keprihatinan, masa- lah terkait-akademik, pribadi, depresi dan perubahan suasana hati, hubungan romantis, kesejahteraan, hubungan lain, kecemasan, kehilangan, dan peralihan, dialami oleh lebih dari 50% partisipan. Diba- has lebih lanjut temuan rinci, implikasi hasil, dan rekomendasi perbaikan kualitas kehidupan ma- hasiswa.